TREATMENT OF THE PATIENT WITH POLYTRAUMA AND EXTENSIVE DEGLOVING INJURY OF SKIN TISSUE OF THE LOWER LIMB - Ya. V. Gavrishuk; S. I. Mikityuk; A. E. Demko; I. V. Kazhanov; A. V. Nikitin (Вестник хирургии имени И.И. Грекова)
.